ALGORITHMIC SOLUTIONS FOR CONTROL AND INTERLOCKS OF SECONDARY COMMUTATIONS DURING OPERATIONAL SWITCHING IN ELECTRICAL NETWORKS - I. Golovinskii (Вестник Северо-Кавказского федерального университета, 2022)
Theoretical methods of algorithmic solutions for the interlocks of operational switching in electrical networks that depend on the switching state of secondary circuits, are considered. A graph-object approach to CIM models of primary and secondary circuits is demonstrated, which reduces their analysis to the calculation of graphs using simple formulas. Examples of application are given.